Preparation method of polyolefin hollow fiber membrane
Through fast cold pulling and slow heat pulling processes, combined with shaping and multiple stretching processes, the pore structure and dimensional stability of the hollow fiber membrane is optimized, and the problem of degassing effect after solvent residue and dense cortex is solved, and the degassing effect after the introduction of solvent residue and dense cortex is achieved. Hollow fiber membrane with long life and efficient degassing.
Patent Information
- Application Number
- CN202210810868.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-11
- Publication Date
- 2025-01-03
AI Technical Summary
There are solvent or additive residues in the existing hollow fiber membranes during the degassing process, which affects the quality of ultrapure water. The degassing effect decreases after the introduction of the dense cortex and has a short service life.
Using fast cold drawing and slow heat pulling, combined with primary and secondary setting processes, the porosity and cortical density of the inner layer are controlled through multiple cold drawing and heat pulling processes to ensure the hollow fiber membrane's porosity and cortical density. Pore structure and dimensional stability.
It improves the service life and degassing effect of hollow fiber membranes, reduces the influence of dense cortex on degassing effect, and ensures the dimensional stability of membrane filaments and efficient degassing performance.
Smart Images

Figure CN119236700A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of membrane separation technology, and in particular to a method for preparing a polyolefin hollow fiber membrane. Background Art
[0002] With the increasing integration of microelectronics, the requirements for water used in the production process are getting higher and higher. For example, when the integration is 4M, the oxygen content of flushing water is required to be less than 50ppm; when the integration reaches 16M, the oxygen content of flushing water is required to be less than 10ppb. This is because the dissolved oxygen in ultrapure water easily reacts with silicon wafers to generate amorphous silicon oxide, thereby affecting the performance and yield of components, and the higher the integration, the greater the impact of dissolved oxygen. Therefore, how to produce ultrapure water with low oxygen content is one of the current research hotspots.
[0003] With the development of membrane separation technology, a membrane contactor method combining membrane separation technology and degassing technology has emerged to remove gas from water. Compared with traditional degassing methods, membrane separation degassing technology has many advantages, such as small equipment footprint, low equipment operating cost, clean and pollution-free, and no need to add various chemicals. Compared with flat membranes, hollow fiber membranes have a larger gas-liquid two-phase contact area, so they are more suitable for degassing water.
[0004] There are many public documents on the preparation method of porous membrane materials. The patent with the patent publication number of US4247498A records that porous PP membrane materials are prepared by thermally induced phase separation. The patent application document of Tsinghua University with the application publication number of CN103464003A clearly records that the diluent and PP material are blended and extruded to prepare sponge-like porous PP membrane materials. The Chinese patent application with the patent application publication number of CN107297155A discloses that on the basis of the melt-stretching method, the membrane filaments obtained by melt spinning are rapidly cooled and dissolved by solvent extraction, and a porous hollow fiber membrane that penetrates inside and outside is obtained by further stretching and pore-forming steps.
[0005] The above technical solutions all require the use of solvents or various additives. Considering that both solvents and additives are bound to have residues, once these residual solvents or additives are dissolved during the preparation of ultrapure water, they will have a greater impact on the quality of ultrapure water. In addition, although the porous hollow fiber membrane with a microporous structure that penetrates inside and outside has a good degassing effect, it is necessary to ensure that the membrane filaments have good hydrophobicity. Once the membrane filaments are wetted by water, the interface on the membrane surface will be destroyed and the gas-liquid separation ability will be lost, so the service life is often short.
[0006] In order to obtain a longer service life, a dense cortical structure can be introduced on the surface of the membrane filament. However, the introduction of a dense cortical structure has a great influence on the degassing effect of the membrane filament. In order to have a good degassing effect while having a long service life, it is necessary to produce a sufficiently high porosity in the inner layer of the membrane filament during the stretching and pore-forming stage, and the cortical layer remains dense. In addition, during the stretching process, it is also necessary to ensure that the dimensional stability of the membrane filament is high. Summary of the invention
[0007] In order to ensure that the inner layer of the hollow fiber membrane can produce a sufficiently high porosity while the skin layer remains dense and the membrane fibers have high dimensional stability, thereby obtaining a hollow fiber membrane with both service life and degassing effect, the present application provides a method for preparing a polyolefin hollow fiber membrane.
[0008] The present application provides a method for preparing a polyolefin hollow fiber membrane using the following technical solution:
[0009] A method for preparing a polyolefin hollow fiber membrane comprises the following process steps:
[0010] S1, spinning, melt-extrude the polyolefin material, and form a semi-molded product with a hollow inner cavity under the action of a cavity-forming fluid; the polyolefin material is at least one of PP and PE, the glass transition temperature of the polyolefin material is Tg, and the melting point of the polyolefin material is Tm;
[0011] S2, cooling and crystallizing, cooling and crystallizing the semi-formed product obtained in step S1, and winding it to obtain the primary fiber;
[0012] S3, primary shaping, heat-setting the spun fiber obtained in step S2, and obtaining a heat-set semi-finished product after cooling;
[0013] S4, cold drawing to form holes, cold drawing the heat-set semi-finished product obtained in step S3 to obtain a cold-drawn semi-finished product; wherein the cold drawing temperature is (Tg+30) to (Tg+80)°C, the cold drawing elongation is 20 to 40%, and the cold drawing rate is (10 to 30)% / min;
[0014] S5, hot-drawing and hole-expanding, hot-drawing and hole-expanding the cold-drawn semi-finished product obtained in step S4 to obtain a hot-drawn semi-finished product; wherein the hot-drawing temperature is (Tm-60) to (Tm-30)°C, the hot-drawing elongation is 2 to 6 times the cold-drawing elongation, and the hot-drawing rate is not higher than 15% of the cold-drawing rate;
[0015] S6, secondary shaping, subjecting the hot-drawn semi-finished product obtained in step S5 to secondary heat shaping to obtain a hollow fiber membrane.
[0016] By adopting the above technical solution,
[0017] In the present application, the polyolefin material can obtain the primary fiber with low crystallinity in the cortex (i.e., the outer surface of the fiber) and high crystallinity in the inner layer (the internal structure of the fiber except the outer surface) through steps S1-S3. On this basis, the present application specifically adopts a cold drawing process with less pulling and faster pulling in combination with a hot drawing process with more pulling and slower pulling, so that the inner layer has a higher porosity and better pore structure. On the basis of introducing a dense cortex, the specific cold and hot drawing process can make the inner layer of the hollow fiber membrane have a better pore structure. On the basis of introducing a dense cortex, a better inner layer pore structure means a better degassing effect. .
[0018] It should be noted that the cold drawing elongation refers to the fiber length before cold drawing is L0, the fiber length after cold drawing is L1, the elongation in the cold drawing stage △L=L1-L0, and the cold drawing elongation is △L / L0*100%. The cold drawing rate refers to the cold drawing elongation that can be achieved per unit time. For example, if the fiber can be stretched to 130% of the original length in 1 minute (i.e. the cold drawing elongation is 30%), then the cold drawing rate is 30% / min.
[0019] The cold drawing elongation has a great influence on the pore structure of the inner layer. This is because the inner layer has a high degree of crystallinity and is mainly composed of lamellae that can produce pore structures. Therefore, under the action of tensile stress, the amorphous regions between the lamellae are mainly deformed and produce microfibril band structures, forming large pore regions between adjacent lamellae, and the microfibril bands in the large pore regions separate the large pore regions into multiple micropore regions, thereby introducing a large number of pore structures in the inner layer. In order to control the porosity of the inner layer, it is necessary to control the lower and upper limits of the cold drawing elongation to ensure that the lamellae of the inner layer separate during the cold drawing process without causing pore collapse due to excessive stretching.
[0020] Similarly, the cold drawing rate has a great influence on the pore structure of the inner layer. This is because when the cold drawing rate is too high, the tensile stress is easily concentrated, causing the lamellae with short relaxation time to form pore structure first and further expand, while the lamellae with long relaxation time have not yet separated, resulting in uneven pore structure. A cold drawing rate that is too high may even cause the microfiber bands in some pore structures to break, while the remaining lamellae have not yet separated, resulting in poor uniformity and uneven distribution of the pore structure size in the inner layer. When the cold drawing rate is too low, the lamellae in the inner layer have enough time to relax. At this time, part of the tensile stress is used to cause the deformation of the lamellae in the inner layer, and only part of the tensile stress is used to cause the deformation of the amorphous zone between the lamellae and the formation of microfiber bands. Due to the low degree of separation of the lamellae, the pore structure formed is small and too small.
[0021] That is, the appropriate cold drawing rate and the appropriate cold drawing elongation must work together to achieve a good pore structure in the inner layer.
[0022] In addition, in the specific system of the present application, it is also necessary to strictly control the hot drawing process parameters such as hot drawing temperature, hot drawing rate and hot stretching elongation. Moreover, the limitation of hot drawing process parameters must be combined with the cold drawing process parameters. The two are a process of mutual influence and feedback adjustment.
[0023] For example, the hot-drawing rate must be matched with the cold-drawing rate, because different cold-drawing rates produce different pore structures, different internal residual stress conditions, different degrees of separation of the lamellae, and different structures of the microfiber bands, and these conditions will affect the hot-drawing rate in the hot-drawing stage. Therefore, the cold-drawing rate or the hot-drawing rate cannot be adjusted in isolation. Similarly, the hot-drawing elongation and the cold-drawing elongation must also be matched.
[0024] In the system of the present application, the hot pull rate needs to be strictly limited. When the hot pull rate is too low (it can be understood that the so-called hot pull rate here refers to the determination of the cold pull rate, and the hot pull rate is characterized by the multiple of the cold pull rate. Therefore, the hot pull rate is too low, which means that the hot pull rate is too low compared to the cold pull rate), the tensile stress has enough time to act on each region. At this time, the molecular chains of the lamellae and the molecular chains at the boundary of the lamellae and the amorphous region have enough time to relax and be pulled out, so that part of the lamellae is converted into microfiber ligaments, and there are too many microfiber ligament structures and too few lamellae structures, resulting in deterioration of the pore structure. When the hot pull rate is too high (that is, the hot pull rate is too high compared to the cold pull rate), the tensile stress is unevenly distributed, and the molecular chains with longer relaxation time have no time to transform, which ultimately results in only some of the molecular chains with shorter relaxation time being transformed into microfiber ligament structures, and the molecular chains at the boundary of the lamellae and the amorphous region are easily stretched excessively by the concentrated tensile stress, thereby blocking the resulting pore structure, resulting in micropore closure and deterioration of the pore structure.
[0025] In the system of the present application, the thermal stretching elongation needs to be strictly limited. When the thermal stretching elongation is too low (similarly, the thermal stretching elongation is too low when compared to the cold stretching elongation), a large number of lamellae that have not been pulled apart in the cold drawing stage cannot be pulled apart in the hot drawing stage, so the porosity and pore structure are poor; when the thermal stretching elongation is too high, a large number of weaker microfiber ligament structures are broken and merged with adjacent microfiber ligament structures that have not been broken to form a thicker microfiber ligament. In this process, the displacement of the lamellae or even the collapse of the structure will occur, resulting in the destruction of the pore structure of the inner layer of the fiber.
[0026] In addition, the appropriate hot and cold drawing process also has an important influence on the thickness of the cortex and the density of the cortex (it should be noted that it is generally believed that by observing the SEM image of the cortex at 10000X, no obvious pore structure or micropore ratio is ≤5%, that is, the cortex is considered to be dense). In order to improve the degassing efficiency of the hollow fiber membrane, it is necessary not only to control the pore structure of the inner layer, but also to control the ratio of the thickness of the dense cortex to the thickness of the membrane wall, so that the cortex of the final hollow fiber membrane is dense and low in thickness, and the inner layer has a higher porosity and a more reasonable pore structure. The limitation of the hot and cold drawing process parameters in this application can not only ensure a good pore structure of the inner layer, but also ensure a lower thickness of the cortex and a lower porosity on this basis.
[0027] The above limitation is unexpected for the following reasons: One problem associated with existing asymmetric hollow fiber membranes is that, while introducing a dense skin structure on the hollow fiber membrane can improve the service life of the hollow fiber membrane, it is expected that the degassing effect will be significantly reduced.
[0028] However, the present application shows that, in fact, the cold-drawing process of fast-drawing and less-drawing and the hot-drawing process of slow-drawing and more-drawing can optimize the pore structure of the inner layer of the hollow fiber membrane, thereby greatly reducing the influence of the introduction of the dense cortex on its degassing effect. In addition, the stretching process can also significantly improve the dimensional stability of the membrane filament. In addition, the cold-drawing process and the hot-drawing process have a fairly strong correlation, and the process parameters of the cold-drawing stage affect the process parameters of the hot-drawing stage to a large extent. The definition of the hot-drawing process parameters must be combined with the cold-drawing process parameters, and there is even a certain proportional relationship between the two. This is a new design idea with great guiding significance.
[0029] Optionally, in step S3, the primary setting temperature is (Tm-60) to (Tm-20)°C; the primary setting time is 25 to 35 minutes; and the spun fibers are stretched during the primary setting process, and the stretching elongation is 0.5 to 2%.
[0030] Optionally, in step S3, the primary shaping time is 30 minutes; during the primary shaping process, the spun fibers are stretched, and the stretching elongation is 1%.
[0031] By adopting the above technical solution,
[0032] The one-time shaping process has a great influence on the performance of the final hollow fiber membrane. This is because the one-time shaping can eliminate the structural defects in the primary fiber, improve the structural integrity of the fiber, and reduce the possibility of excessive concentration of tensile stress in the subsequent stretching and pore-forming process; and because the temperature of the one-time shaping is high, the molecular chains are more likely to move and rearrange at this time, so that the molecular chains in the amorphous region move toward the lamellae, thereby increasing the thickness of the lamellae, improving the crystallinity of the fiber, and improving the regularity of the crystallization. The increase in crystallinity means that the inner layer porosity of the final hollow fiber membrane is high, and the high regularity and orientation of the crystallization means that the inner layer pore structure of the final hollow fiber membrane is uniform.
[0033] The present application is specific that the one-time shaping process determines the crystallinity, crystal form, orientation and lamella size of the fiber before stretching and hole forming, and the one-time shaping can eliminate the structural defects in the primary fiber, improve the structural integrity of the fiber, and reduce the possibility of excessive concentration of tensile stress in the subsequent stretching and hole forming process.
[0034] The present application specifically applies a small amount of external drawing force to the fiber (drawing elongation is about 1%) and reduces the time for one setting. This is because a small amount of external drawing force can reduce the thermal expansion of the fiber at high temperature, and a small amount of external drawing force can promote the orientation of the lamellae and improve the regularity and orientation of the lamellae. The specifically reduced one-time setting time can reduce the possibility of cortical nucleation, crystal growth and orientation under high temperature and external drawing stress. Thereby reducing the possibility of the cortex forming a pore structure in the subsequent stretching and pore-forming step.
[0035] In addition, it should be noted that although a small amount of stretching force is applied in this application, once the temperature during the primary shaping process is too high, some of the lamellae melt, and a small amount of stretching stress is not enough to make them grow into lamellae during recrystallization. Therefore, in the primary shaping step, the temperature, time, and applied stretching force affect and constrain each other.
[0036] Optionally, in step S6, the secondary setting temperature is higher than the primary setting temperature, and the difference between the two is 10-20° C.; the secondary setting time is 0.5-3 min.
[0037] By adopting the above technical solution, the process parameters of the primary shaping and the secondary shaping are also interrelated. This is because the crystallinity, crystal form, regularity, etc. of the fiber after the primary shaping have a great influence on the pore structure of the fiber. Different sheet crystal thicknesses, different microfiber tie sizes, etc. require different process parameters for the secondary shaping.
[0038] The present application limits the secondary setting temperature to 10 to 20°C higher than the primary setting temperature, and specifically limits a shorter secondary setting temperature. This is because the inventor unexpectedly discovered that in the system of the present application, this temperature and this processing time can effectively eliminate the residual stress in the stretching pore-forming stage without destroying the lamellar crystals and pore structure (too high temperature, too long processing time, etc. can easily cause melt recrystallization of thin lamellar crystals and microfiber tie structures, thereby causing destruction of the lamellar structure and pore structure).
[0039] Optionally, the polyolefin material is PP, and in step S3, the primary setting temperature is 100-145°C; the primary fiber is stretched during the primary setting process, and the stretching elongation is 0.8-1.2%; in step S6, the secondary setting temperature is 120-165°C.
[0040] By adopting the above technical solution,
[0041] This application specifically defines various process parameters of PP materials. For PP materials, the primary shaping temperature is limited to 100-145°C, the stretching elongation during shaping is limited to 0.8-1.2%, and the secondary shaping temperature is limited to 120-165°C. The above limitations enable the inner layer of the fiber to have a higher degree of crystallinity, good crystalline regularity and orientation after the primary shaping, so that a good pore structure can be obtained during stretching and forming holes, and during the secondary shaping, the residual stress in the inner layer of the fiber can be well eliminated, so that the fiber and the pore structure on the fiber have a high degree of stability. As for the cortex of the fiber, the specific primary shaping temperature can reduce the crystallinity, crystalline orientation and regularity of the cortex, thereby reducing the possibility of the cortex generating a pore structure during the stretching and forming process.
[0042] Optionally, in step S4, the cold drawing to form holes is performed in 2 to 4 times; the cold drawing temperature is 20 to 40° C.; the cold drawing draft ratio of each cold drawing is 104.7 to 118.3%; and the line speed of the cold drawn semi-finished product at the end of the cold drawing is 2.5 to 3.5 m / min.
[0043] Optionally, in step S4, each cold drawing to form holes includes 3 to 5 stretching stages.
[0044] By adopting the above technical solution, the inventors unexpectedly discovered that compared with single cold drawing, multiple cold drawing can significantly improve the pore structure of the inner layer and cortex of the prepared hollow fiber, wherein the density of the cortex is improved, while the porosity and pore structure of the inner layer are improved.
[0045] This may be because, although the total cold drawing rate and cold drawing elongation of multiple cold drawing are the same as those of single cold drawing, the multiple cold drawing method is actually a process in which the cold drawing rate is continuously increasing. For example, if the cold drawing rate of a single cold drawing is defined as V0, the total cold drawing rate of multiple cold drawing should also be V0, then there must be a cold drawing stage with a stretching rate less than V0 and a cold drawing stage with a stretching rate greater than V0. Correspondingly, during the multiple cold drawing process, the tensile stress is also a process of gradually increasing.
[0046] For the cortex, it is first stretched with a small tensile stress and then stretched with a gradually increased tensile stress. Due to the multiple cold-drawing processes, the stress has time to disperse and the defects have time to relax under the tensile stress, thus greatly reducing the possibility of tensile stress concentrating at the cortex defects and causing a porous structure in the cortex.
[0047] For the inner layer, multiple cold drawing can pull different lamellae apart in stages and step by step. The lamellae that are easy to pull apart are first pulled apart by the small tensile stress, while the lamellae that are difficult to pull apart are pulled apart by the subsequent tensile stress that becomes larger. Since the molecular chain has enough time to relax, the problems of microfiber ties being broken and thick lamellae being difficult to pull apart are greatly reduced, thereby obtaining a larger porosity and a better pore structure. The degassing effect of the hollow fiber membrane is also better.
[0048] It is understandable that the aforementioned, the cold drawing rate is getting faster and faster means that even if the cold drawing draft ratio of each cold drawing is the same, since the original length of the fiber in the next cold drawing is the fiber length after the previous cold drawing, the original length of the fiber is constantly increasing, that is, the base number is constantly increasing. Even if the draft ratio remains unchanged, the absolute value of the cold drawing elongation of the two cold drawing is also increasing. Correspondingly, the cold drawing rate of the two cold drawing is also getting faster. For example, the first cold drawing stretches the original 100% length of the fiber to 120% (that is, the cold drawing draft ratio is 120%), then, if the cold drawing draft ratio of the second cold drawing is still 120%, then, the fiber length after the second cold drawing should be 120%*120%=141%, so its cold drawing rate is actually a process of continuous growth.
[0049] Furthermore, the inventor unexpectedly discovered that, compared to each cold-drawn hole being one stretch, subdividing each cold-drawn hole into 3 to 5 stretches can significantly optimize the pore structure and pore uniformity of the fiber inner layer, and can also reduce the porosity of the cortex. This may be because further subdividing each cold-drawn hole into 3 to 5 stretches can further improve the fineness of the tensile stress growth, thereby further solving the problem of tensile stress concentration caused by excessive tensile stress changes, thereby obtaining a better microporous effect. It should be noted that each cold-drawn hole should not be further subdivided. This is because, although further subdivision can further improve the fineness of tensile stress growth, the growth of tensile stress is too slow, the molecular chains have enough time to relax, and the separation effect of the lamellae is significantly deteriorated.
[0050] It should be noted that each cold-drawing hole-forming operation mentioned above includes 3 to 5 stretching stages, which means that the equipment for cold-drawing operation has 4 to 6 stretching rollers. When the fiber passes through the front and rear two stretching rollers, due to the difference in speed of the two stretching rollers (that is, the aforementioned stretching ratio), the cold-drawing equipment with 4 stretching rollers performs 3 cold-drawing operations, while the cold-drawing equipment with 6 stretching rollers performs 5 cold-drawing operations.
[0051] Optionally, in step S5, the hot drawing temperature is 120-130° C.; the hot drawing elongation is 90-120%; and the hot drawing rate is (1-4.5)% / min.
[0052] By adopting the above technical solution, for the specific system of the present application, the heat-drawing temperature and the heat-drawing elongation largely affect the final thickness of the skin layer, and thus largely affect the degassing efficiency and damage sensitivity of the hollow fiber membrane finally obtained.
[0053] The inventors found that when the present application specifically selects multiple cold drawing processes to cold draw the fibers, the above hot drawing parameters can not only obtain a uniform and good pore structure, but also obtain a good microfiber lacing structure, and in addition, the thickness and density of the skin layer are also more appropriate. Therefore, the hollow fiber membrane finally obtained has better degassing efficiency and lower damage sensitivity.
[0054] Optionally, in step S5, the hot drawing hole expansion is carried out in 3 to 6 times; the hot drawing drafting ratio of each hot drawing is 111.3 to 128.1%; and the line speed of the hot drawn semi-finished product at the end of hot drawing is 4.5 to 7.5 m / min.
[0055] Optionally, in step S5, each hot-drawing hole expansion includes 29 to 31 stretching stages.
[0056] By adopting the above technical solution, after subdividing the cold-drawing pore-inducing into multiple cold-drawings, the inventors of the present application found that subdividing the hot-drawing pore-expanding into multiple hot-drawings can also make the finally prepared hollow fiber membrane have higher degassing efficiency and lower damage sensitivity. Its mechanism is similar to subdividing the cold-drawing pore-inducing into multiple cold-drawings. Since the growth of tensile stress is more delicate, the damage of stress concentration to the microfiber tie and lamellar structure can be reduced.
[0057] In addition, unlike each cold-drawing hole-forming process, which is best divided into 3 to 5 sections, each hot-drawing hole-expansion process is better divided into 29 to 31 sections, which is very different from the number of sections of cold-drawing hole-forming process. This may be due to the low temperature in the cold-drawing stage, the weak mobility of the molecular chains, and the fact that the lamellae are in a basically closed state during the cold-drawing stage, which requires a large stress to pull the lamellae apart and stretch the amorphous areas between the lamellae into microfiber ligaments. The temperature in the hot-drawing stage is high, the mobility of the molecular chains is strong, and stress concentration is more likely to lead to the destruction of the lamellae and the breakage of the microfiber ligaments, etc. In addition, a large number of lamellae have been pulled apart during the cold-drawing stage, and it is not suitable to further apply greater tensile stress. Therefore, the hot-drawing hole-expansion stage requires a significantly more delicate tensile stress growth method than the cold-drawing hole-expansion stage.
[0058] Optionally, step S2 includes the following steps:
[0059] S21, natural cooling, cooling the semi-formed product obtained in step S1 by natural cooling to obtain a naturally cooled semi-finished product; the surface temperature of the naturally cooled semi-finished product obtained after natural cooling is Tm~(Tm+20)°C;
[0060] S22, air cooling crystallization, air cooling crystallization is performed on the naturally cooled semi-finished product obtained in step S21 by means of air cooling, and then rolled up to obtain the spun fiber.
[0061] Optionally, step S22 is divided into a rapid cooling zone and a slow cooling zone, and the cooling rate of the fiber in the rapid cooling zone is not less than 100°C / mm@(100-200)m / min.
[0062] By adopting the above technical solution, the specific hot and cold drawing process of this application is combined with the specific spinning cooling process of this application, so that the hollow fiber membrane finally obtained can have a dense and thin skin layer and a microporous inner layer. By controlling the thickness of the skin layer and the pore structure of the inner layer, the influence of the dense skin layer on the degassing effect can be reduced, so that even if the hollow fiber membrane of this application introduces a dense skin layer, the degassing effect is less reduced, and the service life is significantly improved.
[0063] The present application limits the cooling rate of the fiber in the rapid air cooling stage to ensure that the fiber cortex thickness is low and basically maintains a dense structure during the stretching and pore-forming stage, and the inner layer of the fiber will produce a large number of microporous structures. The dense cortex structure can increase the service life of the hollow fiber membrane; the low-thickness cortex and the inner layer with a large porosity can ensure that the hollow fiber membrane has a good degassing effect. As a result, the hollow fiber membrane of the present application has a significantly longer service life and only a slightly reduced degassing effect.
[0064] It should be noted that the cooling rate in this application is not less than 100°C / mm@(100-200)m / min, which means that when the fiber linear speed is 100-200m / min, the temperature reduction value is not less than 100°C in a cooling path of 1mm.
[0065] Optionally, in step S21, the length of the natural cooling path is 30 to 1000 mm; the atmosphere during natural cooling is air or nitrogen, and the atmosphere temperature during natural cooling is 40 to 70°C; the cooling rate of the surface of the semi-molded product during natural cooling is (0.05 to 0.6)°C / mm@(100 to 200)m / min.
[0066] By adopting the above technical solution, as the temperature decreases during natural cooling of the fiber, the viscosity of the material increases rapidly, and accordingly, the dimensional stability of the fiber also increases rapidly. In addition, as the viscosity of the material increases, the macromolecular chain segments produce preliminary orientation under the action of the drawing stress, making it easier to generate a lamellar structure that can be stretched into holes. Since the viscosity of the material is mainly limited by the temperature of the material, it is necessary to strictly limit the various process parameters during natural cooling to ensure that a larger number of microporous structures can be formed in the inner layer of the hollow fiber membrane, so as to improve the degassing effect of the hollow fiber membrane while ensuring a longer service life.
[0067] Optionally, in step S22, the speed of the cooling air flow is 30-60 m / min; the temperature of the cooling air flow is 40-70°C.
[0068] Optionally, in step S22, the wind direction of the cooling airflow is inclined along the conveying direction of the naturally cooled semi-finished product and falls in the rapid cooling zone; the angle formed by the wind direction of the cooling airflow and the axis of the naturally cooled semi-finished product is 30 to 70°; the path length of the slow cooling zone is 4 to 8 m.
[0069] By adopting the above technical solution, the speed and temperature of the cooling air flow need to match the winding speed of the fiber. The faster the fiber winding speed, the faster the cooling air flow should be, so that the cooling speed of the fiber surface can be controlled at the required level of not less than 100°C / mm@(100-200)m / min.
[0070] Furthermore, the inventors unexpectedly discovered that, compared with setting the cooling airflow to be perpendicular to the fibers and sweeping the fibers, setting the cooling airflow direction to form a certain angle with the fibers can obtain a hollow fiber membrane with higher dimensional stability, lower skin thickness and better pore structure.
[0071] This may be because, when the cooling airflow sweeps to the fiber surface (that is, in the rapid cooling zone), the surface of the fiber quickly cools down and solidifies, thereby forming a cortex with low crystallinity; however, in order to avoid the problem of excessive cortex thickness and excessive cooling of the inner layer of the fiber, which leads to a decrease in crystallinity, it is necessary to avoid further rapid cooling of the fiber surface. The specific cooling airflow direction of the present application is set so that the temperature of the cooling airflow rises after rapid heat exchange with the fiber in the rapid cooling zone. Since the wind direction of the cooling airflow is the same as the fiber conveying direction and is at a certain angle, the heated cooling airflow will continue to sweep a certain distance in the direction of fiber conveying, thereby forming an air film on the fiber surface with a higher temperature than the environment, so as to reduce the cooling rate of the fiber in the slow cooling zone, reduce the thickness of the fiber cortex, and give the inner layer enough time to complete crystallization and orientation of the lamellae. A thinner cortex combined with an inner layer with a larger porosity can make the hollow fiber membrane have better degassing efficiency and a longer service life.
[0072] In summary, the present application includes at least one of the following beneficial technical effects:
[0073] 1. By adopting a specific rapid cold drawing and slow hot drawing stretching and pore forming process, the pore structure of the inner layer of the hollow fiber membrane can be optimized, thereby obtaining a hollow fiber membrane with excellent service life and degassing effect.
[0074] 2. The present application specifically controls the one-time shaping process, especially applies a small amount of stretching external force and reduces the one-time shaping time during the one-time shaping process, which can not only reduce the expansion of the membrane filament during the one-time shaping, but also promote the elimination of membrane filament defects and improve the orientation of the inner layer lamellae of the membrane filament, while having almost no effect on the crystallinity of the membrane filament cortex, ensuring that the cortex remains dense and the inner layer has a higher porosity.
[0075] 3. By associating the process parameter adjustments of the primary shaping process and the secondary shaping process, compared with adjusting the process parameters of the primary shaping process and the secondary shaping process independently, the stability of the inner layer microporous structure can be ensured, thereby improving the degassing effect of the hollow fiber membrane.
[0076] 4. By adopting a special cold drawing process of multiple cold drawing and multi-stage stretching in one cold drawing, the porosity of the inner layer can be significantly optimized while ensuring the density of the cortex, so that the hollow fiber membrane has a better degassing effect, ensuring that the hollow fiber membrane has a longer service life and the degassing effect decreases less.
[0077] 5. By adopting a specific multiple hot-drawing process, a special hot-drawing process of multiple stretching in one hot-drawing can reduce the possibility of microporous structure in the cortex while ensuring that the size of the inner micropores is enlarged and the porosity is further improved, so as to ensure that the hollow fiber membrane has a good degassing effect and a longer service life.
[0078] 6. By controlling the cooling rate of the membrane filaments after melt spinning, it can be ensured that the final hollow fiber membrane has a more appropriate skin thickness, so as to reduce the influence of too thick skin on the degassing effect and the influence of too thin skin on the service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0079] Figure 1 This is a SEM image of the outer surface of the hollow fiber membrane prepared in Example 8 of the present application, and the magnification is 10000X.
[0080] Figure 2 This is a SEM image of the inner surface of the hollow fiber membrane prepared in Example 8 of the present application, and the magnification is 10000X. DETAILED DESCRIPTION
[0081] The following is combined with Figures 1-2 This application is described in further detail.
[0082] Unless otherwise specified, in the following examples, the raw materials and equipment used to prepare the hollow fiber membranes can be purchased from commercial sources. The structure and morphology of the membranes were characterized using a scanning electron microscope (S-5500) provided by Hitachi.
[0083] It should be noted that since the hollow fiber membrane prepared in this application is mainly used in the degassing step in the ultrapure water preparation process (of course, it can also be applied to degassing in other fields), due to the characteristics of ultrapure water, the seepage effect of the hollow fiber membrane needs to be strictly controlled. For example, when preparing hollow fiber membranes by methods such as thermally induced phase separation and liquid cold extraction, solvents need to be used, and some of the solvents must remain in the prepared hollow fiber membranes (even after post-treatment and desolvation). This part of the solvent is likely to seep out during the ultrapure water degassing treatment, resulting in ultrapure water contamination. For example, in order to obtain better mechanical properties, various additives such as fillers, nucleating agents, etc. are added to polyolefin materials. Similarly, although the above-mentioned additives can improve the mechanical properties of the prepared hollow fiber membranes to a certain extent, the risk of impurity seepage is contrary to the purpose of this application.
[0084] On the basis of the above, the embodiment of the present application discloses a method for preparing a polyolefin hollow fiber membrane. Preferably, the hollow fiber membrane can be used for degassing of ultrapure water.
[0085] The embodiment of the present application discloses a method for preparing a polyolefin hollow fiber membrane.
[0086] Example 1
[0087] In this embodiment, the polyolefin material is PE, and more preferably, commercially available mLLDPE (metallocene linear low-density polyethylene) is used. The mLLDPE has a crystallinity of 68% (measured by DSC method) and a density of 0.93 g / cm 3 , molecular weight is 60000, molecular weight distribution index is about 2.3, melt index is 4.5g / min@(130℃, 5kg). In addition, the melting point Tm of mLLDPE is about 119℃, and the glass transition temperature Tg is -38℃.
[0088] The preparation process of the hollow fiber membrane for degassing using the above mLLDPE as raw material comprises the following process steps:
[0089] S1, spinning, put the above mLLDPE into an extruder for melt mixing, melt mixing includes melting, mixing and metering in sequence, and the temperature is set to 135°C, 125°C and 150°C respectively. After melt mixing, the molten material is extruded into fibers, and a vertical downward spinning extrusion method is adopted. A hollow die is used during extrusion, and a cavity fluid is injected into the hollow inner cavity of the die. In this embodiment, the cavity fluid is nitrogen (the cavity fluid can also be other inert gases, or even liquid fluids), and the outlet wall thickness of the material on the die is 2mm (i.e., the wall thickness is 2mm when extruded into fibers). The die temperature is 140°C, and the die aspect ratio is 5. Under the action of the cavity fluid, the material is extruded to form a semi-molded product with a hollow inner cavity. At this time, the semi-molded product is still in liquid.
[0090] S2, cooling crystallization, cooling crystallization is divided into natural cooling and air cooling crystallization performed in sequence, that is, step S2 includes the following process steps:
[0091] S21, natural cooling, the semi-molded product obtained by extruding the molten material is exposed to the air (of course, the atmosphere can also be controlled to be an inert gas such as nitrogen) for preliminary natural cooling, and is naturally cooled until the surface temperature of the fiber is about 125°C, and the natural cooling is completed to obtain a naturally cooled semi-finished product. In this process, the natural cooling path length is controlled to be 300mm, and the temperature of the atmosphere around the semi-molded product is controlled to be 70°C, and the cooling rate of the fiber surface is about 0.05°C / mm@(120m / min).
[0092] S22, air cooling crystallization, after the fiber surface is cooled to a temperature close to the melting point of the material to obtain a naturally cooled semi-finished product, the fiber is further cooled by blowing cooling to cause the fiber to undergo cooling crystallization. In this step, the speed of the cooling airflow is 33m / min, the temperature of the cooling airflow is 70°C, the wind direction of the cooling airflow is inclined toward the direction of fiber conveying, and the angle formed by the wind direction of the cooling airflow and the axis of the fiber is 60°.
[0093] It should be noted that the air-cooling crystallization in this step is divided into two sections, namely the rapid cooling zone and the slow cooling zone. The area where the cooling airflow moves along its wind direction and directly contacts the fiber is considered to be the rapid cooling zone. The cooling airflow and the fiber produce rapid heat exchange in this area, so that the surface of the fiber is rapidly cooled; the area from the fiber passing through the rapid cooling zone to the winding is considered to be the slow cooling zone. After the fiber passes through the rapid cooling zone and the slow cooling zone in turn, it is wound to obtain the nascent fiber.
[0094] After the fiber passes through the rapid cooling zone, the surface temperature drops to about 80°C, and then passes through the slow cooling zone with a path length of 6m for winding. The winding speed is 120m / min (i.e., spinning speed), and the nozzle stretch ratio is 40. The cooling rate of the fiber in the rapid cooling zone is 150°C / mm@(120m / min).
[0095] It should be noted that the boundary between the rapid cooling zone and the slow cooling zone is determined based on the cooling rate of the fiber surface. When the cooling rate of the fiber surface decreases significantly, it is considered that the fiber has entered the slow cooling zone from the rapid cooling zone.
[0096] S3, primary setting, the spun fibers obtained by winding are subjected to the first heat setting treatment, the heat setting temperature is 95°C, the heat setting time is 30 minutes, during the heat setting process, an external force is applied to the spun fibers for stretching, and the stretching elongation is 1%. After the first heat setting treatment of the spun fibers, a heat-set semi-finished product is obtained.
[0097] S4, cold drawing to cause pores. After the primary fiber has been treated with the first heat setting, the defects in the fiber are roughly eliminated. At this time, the fiber can be cold drawn to initially produce a microporous structure in the inner layer with a higher degree of fiber crystallinity. In the cold drawing to cause pores stage, a single cold drawing process is adopted, with a cold drawing elongation of 30%, a cold drawing rate of 20% / min, and a cold drawing temperature of 25°C. After cold drawing, a cold drawn semi-finished product is obtained, and the line speed of the cold drawn semi-finished product is 3m / min.
[0098] S5, hot-drawing hole expansion, after the fiber is cold-drawn, the inner layer of the lamellae separates and produces a microporous structure, which can be further hot-drawn to expand the produced microporous structure. In addition, hot-drawing can further pull apart the lamellae that have not been separated during the cold-drawing process, thereby producing a larger number of microporous structures in the inner layer of the fiber. In the hot-drawing hole expansion stage, a hot-drawing process is adopted, the hot-drawing elongation is 100%, the hot-drawing rate is 2% / min, the hot-drawing temperature is 85°C, and the hot-drawn semi-finished product is obtained after hot-drawing. At this time, the line speed of the hot-drawn semi-finished product is 6m / min.
[0099] S6, secondary shaping, after the fiber is cold and hot drawn, the microporous structure of the inner layer is basically formed, but once the drawing force is removed, the fiber is easy to shrink, resulting in a reduction in the microporous structure or even partial closure. Therefore, the fiber needs to be heat-set for the second time after the cold and hot drawing treatment. In the second heat setting stage, the heat setting temperature is 115℃, the heat setting time is 1.5min, and the hollow fiber membrane is obtained by natural cooling after the heat setting.
[0100] Example 2
[0101] In this embodiment, the polyolefin material is PP, preferably isotactic homopolymer PP, the crystallinity of the PP is 50% (measured by DSC method), the isotacticity is 99.9%, the molecular weight is about 80,000, the molecular weight distribution index is 1.5, and the melt index is about 2g / min@(190°C, 5kg). In addition, the melting point Tm of the PP is about 168°C, and the glass transition temperature Tg is -10°C.
[0102] The preparation process of the hollow fiber membrane for degassing using the above PP as raw material includes the following process steps:
[0103] S1, spinning, put the above PP into the extruder for melt mixing, melt mixing includes melting, mixing and metering in sequence, and the temperatures are set to 165°C, 200°C and 205°C respectively. After melt mixing, the molten material is extruded into fibers, and a vertical downward spinning extrusion method is adopted. A hollow die is used during extrusion, and a cavity-forming fluid is injected into the hollow inner cavity of the die. In this embodiment, the cavity-forming fluid is nitrogen, and the outlet wall thickness of the material on the die is 2mm (that is, the wall thickness is 2mm when extruded into fibers). The die temperature is 190°C, and the die aspect ratio is 4. Under the action of the cavity-forming fluid, the material is extruded to form a semi-molded product with a hollow inner cavity. At this time, the semi-molded product is still in liquid state.
[0104] S2, cooling crystallization, cooling crystallization is divided into natural cooling and air cooling crystallization performed in sequence, that is, step S2 includes the following process steps:
[0105] S21, natural cooling, the semi-molded product obtained by extruding the molten material is exposed to the air for preliminary natural cooling, and is naturally cooled until the surface temperature of the fiber is about 170°C, and the natural cooling is completed to obtain a naturally cooled semi-finished product. In this process, the natural cooling path length is controlled to be 100mm, and the temperature of the atmosphere around the semi-molded product is controlled to be 60°C, and the cooling rate of the fiber surface is about 0.2°C / mm@(150m / min).
[0106] S22, air cooling crystallization, after the fiber surface is cooled to a temperature close to the melting point of the material to obtain a naturally cooled semi-finished product, the fiber is further cooled by blowing cooling to cause the fiber to undergo cooling crystallization. In this step, the speed of the cooling airflow is 40m / min, the temperature of the cooling airflow is 60°C, the wind direction of the cooling airflow is inclined toward the direction of fiber conveying, and the angle formed by the wind direction of the cooling airflow and the axis of the fiber is 50°.
[0107] It should be noted that the air-cooling crystallization in this step is divided into two sections, namely the rapid cooling zone and the slow cooling zone. The area where the cooling airflow moves along its wind direction and directly contacts the fiber is considered to be the rapid cooling zone. The cooling airflow and the fiber produce rapid heat exchange in this area, so that the surface of the fiber is rapidly cooled down; the area from the fiber passing through the rapid cooling zone to the winding is considered to be the slow cooling zone. After the fiber passes through the rapid cooling zone and the slow cooling zone in turn, it can be wound up to obtain the nascent fiber.
[0108] After the fiber passes through the rapid cooling zone, the surface temperature drops to about 90°C, and then passes through the slow cooling zone with a path length of 8m for winding. The winding speed is 150m / min (i.e., spinning speed), and the nozzle stretch ratio is 40. The cooling rate of the fiber in the rapid cooling zone is 200°C / mm@(150m / min).
[0109] It should be noted that the angle between the cooling airflow and the fiber is different, and the width of the rapid cooling zone also changes slightly. Therefore, the boundary between the rapid cooling zone and the slow cooling zone is determined based on the cooling rate on the fiber surface. When the cooling rate on the fiber surface decreases significantly, it is considered that the fiber has entered the slow cooling zone from the rapid cooling zone.
[0110] S3, primary setting, the spun fibers obtained by winding are subjected to the first heat setting treatment, the heat setting temperature is 130°C, the heat setting time is 30 minutes, and during the heat setting process, the spun fibers are subjected to a drafting treatment, and the drafting elongation is 1%. After the first heat setting treatment of the spun fibers, a heat-set semi-finished product is obtained.
[0111] S4, cold drawing to cause pores. After the primary fiber has been subjected to the first heat setting treatment, the defects in the fiber are roughly eliminated. At this time, the fiber can be cold drawn to initially produce a microporous structure in the inner layer with a higher degree of fiber crystallinity. In the cold drawing to cause pores stage, a single cold drawing process is adopted, with a cold drawing elongation of 30%, a cold drawing rate of 20% / min, and a cold drawing temperature of 30°C. After cold drawing, a cold drawn semi-finished product is obtained, and the line speed of the cold drawn semi-finished product is 3m / min.
[0112] S5, hot-drawing hole expansion, after the fiber is cold-drawn, the inner layer of the lamellae separates and produces a microporous structure, which can be further hot-drawn to expand the produced microporous structure. In addition, hot-drawing can further pull apart the lamellae that have not been separated during the cold-drawing process, thereby producing a larger number of microporous structures in the inner layer of the fiber. In the hot-drawing hole expansion stage, a hot-drawing process is adopted, the hot-drawing elongation is 100%, the hot-drawing rate is 2.4% / min, the hot-drawing temperature is 120°C, and the hot-drawn semi-finished product is obtained after hot-drawing. At this time, the line speed of the hot-drawn semi-finished product is 6m / min.
[0113] S6, secondary shaping, after the fiber is cold and hot drawn, the microporous structure of the inner layer is basically formed, but once the drawing force is removed, the fiber is easy to shrink, resulting in a reduction in the microporous structure or even partial closure. Therefore, the fiber needs to be heat-set for the second time after the cold and hot drawing treatment. In the second heat setting stage, the heat setting temperature is 140°C, the heat setting time is 2 minutes, and the hollow fiber membrane is obtained by natural cooling after the heat setting is completed.
[0114] Example 3
[0115] The main difference between Example 3 and Example 2 is that the secondary setting temperature in step S6 is 5° C. higher than the primary setting temperature in step S3 , that is, the secondary setting temperature is 135° C.
[0116] Example 4
[0117] The main difference between Example 4 and Example 2 is that a secondary cold drawing process is used when cold drawing to form holes, that is, step S4 includes the following process steps:
[0118] S4, cold drawing to cause holes, in the cold drawing to cause holes stage, a secondary cold drawing process is adopted, the total cold drawing elongation after two cold drawing is still 30%, the average cold drawing rate of the two cold drawing is still 20% / min, the cold drawing temperature is still 30°C, and a cold drawn semi-finished product is obtained after the cold drawing is completed. Among them, the cold drawing draft ratio during the two cold drawing is 114%, and the line speed of the cold drawn semi-finished product is 3m / min at the end of the cold drawing.
[0119] Example 5
[0120] The main difference between Example 5 and Example 4 is that when cold drawing to form holes, each cold drawing includes 4 stretching stages. When the fiber passes through the front and rear stretching rollers, the fiber is stretched due to the difference in speed between the two stretching rollers. That is, when the stretching equipment for cold drawing has different numbers of stretching rollers, different numbers of stretching stages can be performed in one cold drawing operation. The equipment of Example 4 has 2 stretching rollers (1 stretching stage), while the equipment of this embodiment has 5 stretching rollers (4 stretching stages).
[0121] Example 6
[0122] The main difference between Example 6 and Example 5 is that, on the basis that each cold drawing includes four stretching stages, four cold drawing processes are used when cold drawing to form holes, that is, step S4 includes the following process steps:
[0123] S4, cold drawing to cause holes, in the cold drawing to cause holes stage, four cold drawing processes are adopted, the total cold drawing elongation after four cold drawing is still 30%, the average cold drawing rate of four cold drawing is still 20% / min, the cold drawing temperature is still 30°C, and the cold drawing semi-finished product is obtained after the cold drawing. Among them, the cold drawing draft ratio during the four cold drawing is 107%, and the line speed of the cold drawing semi-finished product is 3m / min at the end of cold drawing.
[0124] Example 7
[0125] The main difference between Example 7 and Example 5 is that a three-step hot-drawing process is used during hot-drawing hole expansion, that is, step S5 includes the following process steps:
[0126] S5, hot drawing and hole expansion, in the hot drawing and hole expansion stage, three hot drawing processes are adopted, the total hot drawing elongation after three hot drawing is still 100%, the average hot drawing rate of three hot drawing is still 2.4% / min, the hot drawing temperature of three hot drawing is 120°C, and the hot drawing semi-finished product is obtained after hot drawing. Among them, the hot drawing draft ratio during the three hot drawing is 126%, and the line speed of the hot drawn semi-finished product after the hot drawing is 6m / min.
[0127] Example 8
[0128] The main difference between Example 8 and Example 7 is that during hot-drawing hole expansion, each hot-drawing includes 30 stretching stages. That is, when the stretching equipment for hot-drawing operation has different numbers of stretching rollers, different numbers of stretching stages can be performed in one hot-drawing operation. The equipment of Example 7 has 2 stretching rollers (1 stretching stage), while the equipment of this example has 31 stretching rollers (30 stretching stages).
[0129] Example 9
[0130] The main difference between Example 9 and Example 8 is that during hot-drawing hole expansion, each hot-drawing includes 5 stretching stages, that is, the device of Example 8 has 31 stretching rollers (30 stretching stages), while the device of this example has 6 stretching rollers (5 stretching stages).
[0131] Example 10
[0132] The main difference between Example 10 and Example 8 is that, on the basis that each hot drawing includes 30 stretching stages, six hot drawing processes are used during hot drawing and hole expansion, that is, step S5 includes the following process steps:
[0133] S5, hot drawing and hole expansion, in the hot drawing and hole expansion stage, six hot drawing processes are adopted, the total hot drawing elongation after six hot drawing is still 100%, the average hot drawing rate of six hot drawing is still 2.4% / min, the hot drawing temperature of six hot drawing is 120°C, and the hot drawing semi-finished product is obtained after hot drawing. Among them, the hot drawing draft ratio during the six hot drawing is 112%, and the line speed of the hot drawn semi-finished product after the hot drawing is 6m / min.
[0134] Examples 11-13
[0135] The main difference between Examples 11-13 and Example 8 is that the process parameters of step S4 and step S5 are different. The process parameters are recorded in the following table:
[0136]
[0137] That is, in Example 8, the hot stretching elongation is about 3.3 times the cold stretching elongation, and the hot drawing rate is 12% of the cold drawing rate; the cold stretching elongation of each cold drawing is 114%, and the hot drawing draw ratio of each hot drawing is 126%.
[0138] As for Example 11, the hot drawing elongation is about 6 times the cold drawing elongation, and the hot drawing rate is 14% of the cold drawing rate; the cold drawing elongation of each cold drawing is 120%, and the hot drawing draw ratio of each hot drawing is 130%; and the hot drawing process parameters are modified based on the cold drawing process parameters.
[0139] As for Example 12, the hot drawing elongation is about twice the cold drawing elongation, and the hot drawing rate is 6% of the cold drawing rate; the cold drawing elongation of each cold drawing is 118%, and the hot drawing draw ratio of each hot drawing is 122%; and the hot drawing process parameters are modified based on the cold drawing process parameters.
[0140] For Example 13, the hot stretching elongation is about 4 times the cold stretching elongation, and the hot drawing rate is 12% of the cold drawing rate; the cold stretching elongation of each cold drawing is 112%, and the hot drawing draw ratio of each hot drawing is 126%; and the hot drawing process parameters are modified based on the cold drawing process parameters.
[0141] Comparative Example
[0142] Comparative Example 1
[0143] The main difference between Comparative Example 1 and Example 11 is that the total hot stretching elongation in the hot drawing hole expansion stage is 8 times the total cold stretching elongation in the cold drawing hole forming stage, and the hot drawing rate is 20% of the cold drawing rate.
[0144] That is, in step S4, the cold drawing elongation is 20% and the cold drawing rate is 15% / min;
[0145] In step S5, the heat-drawing elongation is 160% and the heat-drawing rate is 3% / min.
[0146] Comparative Example 2
[0147] The main difference between Comparative Example 2 and Example 8 is that the total cold drawing elongation in the cold drawing hole-inducing stage is 50%, and the cold drawing rate is 40% / min; however, the hot drawing elongation is still about 3.3 times the cold drawing elongation, and the hot drawing rate is still 12% of the cold drawing rate.
[0148] That is, in step S4, the cold drawing elongation is 50% and the cold drawing rate is 40% / min;
[0149] In step S5, the heat-drawing elongation is 165%, and the heat-drawing rate is 4.8% / min.
[0150] Performance testing methods and performance testing data
[0151] 1. Gas flux detection
[0152] The hollow fiber membranes prepared in the examples or comparative examples were used as raw materials to assemble a membrane with an area of 0.1 m 2 The component is used as a sample to detect the gas flux.
[0153] Gases with a pressure of 0.1 MPa were introduced into the inlet of the component. The gases were oxygen, nitrogen and carbon dioxide respectively. The outlet of the component was connected to a flow meter to record the gas flux of the component per unit time.
[0154] Generally speaking, the larger the gas flux, the better the degassing effect of the component.
[0155] 2. Degassing efficiency and damage sensitivity
[0156] 2.1 Deoxygenation efficiency
[0157] Deoxidation efficiency
[0158] The hollow fiber membranes prepared in the examples or comparative examples were used as raw materials to assemble a membrane having an area of 0.65 m2 The components are connected with the dissolved oxygen meter, water circuit and components for testing. The water circuit is used to transport the degassed liquid, the components are used to degas the degassed liquid, and the dissolved oxygen meter is used to detect the oxygen content of the degassed liquid after degassing. The degassed liquid is deionized water and the temperature of the degassed liquid is 25°C. The inside of the membrane is vacuum purged.
[0159] Step 1: Detect the initial oxygen content of the degassed liquid. Pump the degassed liquid into the water circuit. At this time, turn off the vacuum equipment to make the inner side of the membrane at normal pressure. The degassed liquid passes through the assembly (without degassing) and then the dissolved oxygen meter. Keep the flow rate of the degassed liquid into the dissolved oxygen meter at about 1.8 GLH. Observe the changes in the dissolved oxygen reading on the dissolved oxygen meter in real time. After the reading of the dissolved oxygen meter stabilizes (the reading of the dissolved oxygen meter changes by less than 1% within 5 minutes), read the dissolved oxygen reading on the dissolved oxygen meter. 始 .
[0160] Step 2: Detect the final oxygen content of the degassed liquid after degassing. On the basis of step 1, turn on the vacuum equipment to vacuum purge the inner layer of the membrane to degas the degassed liquid. During the vacuum purge, keep the vacuum reading at -0.094MPa (50torr). Observe the changes in the dissolved oxygen reading on the dissolved oxygen meter in real time. When the reading of the dissolved oxygen meter stabilizes (the reading of the dissolved oxygen meter changes by less than 1% within 5 minutes), the degassing is considered to have reached equilibrium. Read the dissolved oxygen reading on the dissolved oxygen meter. 终 The deoxidation efficiency is calculated by the following formula:
[0161]
[0162] 2.2 Acid damage sensitivity
[0163] On the basis of test method 2.1, the degassing liquid was replaced with a hydrochloric acid solution with a concentration of 5 mol / L. The condition of the component was observed every 4 hours. When leakage occurred on the inner side of the membrane, the component was considered to be breached and lost its degassing ability. The time when the component was breached was recorded.
[0164] 2.3 Alkali damage sensitivity
[0165] On the basis of test method 2.1, the degassing liquid was replaced with a sodium hydroxide solution with a concentration of 5 mol / L. The condition of the component was observed every 4 hours. When leakage occurred on the inner side of the membrane, the component was considered to be breached and lost its degassing ability. The time when the component was breached was recorded.
[0166] 2.4 Resistance to wetting damage sensitivity
[0167] On the basis of test method 2.1, the degassing liquid was replaced with 100% n-butanol (surface tension of 24.6 dynes), and the component was observed every 4 hours. When leakage occurred on the inner side of the membrane, the component was considered to be breached and lost its degassing ability. The time when the component was breached was recorded.
[0168] 3. Mechanical properties
[0169] The tensile properties of the hollow fiber membranes prepared in the embodiments and comparative examples were tested. The two ends of the hollow fiber membranes were clamped with chucks with a distance of 5 cm between the two ends (i.e., the actual test length of the hollow fiber membrane was 5 cm), and the tensile strength and elongation at break of the hollow fiber membranes were tested.
[0170] 3.1 Tensile strength
[0171] Tensile Strength:
[0172] In the formula: σ—tensile strength; Fb—maximum force when breaking; So—original cross-sectional area of the specimen; “specimen area S” is used in the instrument to represent it.
[0173] 3.2 Elongation at break
[0174] Elongation at break:
[0175] Where: e is the elongation at break; △L is the length increment between the gauge lengths of the specimen; L is the gauge length of the specimen.
[0176] The morphological characteristics of each embodiment and comparative example are shown in Table 1:
[0177] Table 1: Film structure morphology characteristics of each embodiment and comparative example
[0178]
[0179] It should be noted that the embodiments in Table 1 with an outer surface porosity of 0 do not mean that there is no microporous structure on the outer surface at all, but rather that the size and number of the microporous structure are almost negligible, and therefore recorded as 0.
[0180] In Table 1, dimensional stability refers to the outer diameter of the hollow fiber membranes prepared in each embodiment or comparative example. The outer diameter of each hollow fiber membrane is measured 3 times, with an interval of 20 cm between each measurement. The maximum value of the outer diameter is recorded as d max , record the smallest outer diameter as d min , the dimensional change rate is calculated according to the following formula:
[0181]
[0182] The smaller the dimensional change rate, the higher the dimensional stability. The performance test data of each embodiment and comparative example are shown in Table 2:
[0183] Table 2 Performance test data of each embodiment and comparative example membrane
[0184]
[0185] in conclusion
[0186] By comparing the technical solutions of Examples 1-2 and the relevant data of Tables 1-2, it is not difficult to see that compared with PE, the hollow fiber membrane of PP material has a significantly larger gas flux. However, the hollow fiber membrane of PE material has a higher gas separation rate. Therefore, the appropriate polyolefin material can be selected according to the needs.
[0187] By comparing the technical solutions of Examples 2-3 and the relevant data of Tables 1-2, it is not difficult to see that there needs to be a certain temperature difference between the temperature during the first shaping treatment and the temperature during the second shaping treatment. If the temperature difference between the two is small (less than 10°C), the second shaping treatment will most likely not be able to eliminate the stress of the fiber well, resulting in fiber shrinkage, fiber size enlargement, and decreased porosity, resulting in a significant decrease in dimensional stability and degassing effect.
[0188] By comparing the technical solutions of Examples 2, 4-6 and the relevant data of Table 1-2, it is not difficult to see that compared with the single cold drawing process, the hollow fiber membrane prepared by the multiple cold drawing process has a significantly better degassing effect, and the dimensional stability of the prepared hollow fiber membrane is also good. Further, on the basis of multiple cold drawing, each cold drawing is performed with multiple stretching stages, which can further optimize the microporous structure of the prepared hollow fiber membrane, thereby obtaining a better degassing effect and better dimensional stability.
[0189] By comparing the technical solutions of Examples 5, 7-10 and the relevant data of Tables 1-2, it is not difficult to see that compared with a single hot-drawing process, the hollow fiber membrane prepared by multiple hot-drawing processes has significantly better degassing effect and dimensional stability. Further, on the basis of multiple hot-drawings, each hot-drawing is performed with multiple stretchings to further optimize the microporous structure of the prepared hollow fiber membrane. Unlike the cold-drawing stage, which is different from the cold-drawing stage in which about 4 stretchings are performed once, the hot-drawing stage needs to be stretched for about 30 stretchings (different from the cold-drawing stage in which 4 stretchings can cause a large performance change, the performance of the hot-drawing stage is slightly different from that of the 1 stretching when the 5 stretchings are stretched in the hot-drawing stage) to obtain the degassing effect of the optimized hollow fiber membrane. This shows that although the absolute operating speed of the hot-drawing stage is faster, the stretching rate of the hot-drawing stage must be much lower than the stretching rate of the cold-drawing stage, which means that in the present application, the hot-drawing stage is actually a large number of stretchings The accumulation of the required hot stretching elongation, such a hot-drawing method can obtain a hollow fiber membrane with better degassing performance and higher dimensional stability.
[0190] By comparing the technical solutions of Examples 8, 11-13 and the relevant data of Table 1-2, it is not difficult to see that the ratio between the cold stretch elongation and the hot stretch elongation, as well as the ratio between the cold drawing speed and the hot drawing speed, must be controlled within a certain range. On this basis, the hollow fiber membrane finally obtained not only has a high service life, but also has good degassing performance and good dimensional stability. Obviously, there is a strong correlation between the cold and hot drawing process parameters. The definition of the hot drawing process parameters must be combined with the cold drawing process parameters, and the two even have a certain proportional relationship. Therefore, in fact, some process parameters of the hot drawing stage (such as hot stretch elongation and hot drawing rate) can even be characterized and defined by the process parameters of the cold drawing stage, which is a new design idea.
[0191] Further comparing the technical solutions of Example 11 with those of Comparative Example 1 and the relevant data of Table 1-2, it is not difficult to see that the proportional relationship between the cold drawing process parameters and the hot drawing process parameters must be strictly controlled. When the ratio of the hot drawing elongation to the cold drawing elongation and the ratio of the hot drawing speed to the cold drawing speed are too high, the pore structure of the obtained hollow fiber membrane is significantly deteriorated, and not only the degassing performance is reduced, the service life is reduced, and the dimensional stability is also significantly reduced. This further proves the correlation between the process parameters in the cold drawing stage and the hot drawing stage.
[0192] Further comparing the technical solutions of Example 8 and Comparative Example 2 and the relevant data of Tables 1-2, it is not difficult to see that, on the basis that the proportional relationship between the cold-drawing process parameters and the hot-drawing process parameters conforms to the specific definition of this application, the cold-drawing process parameters and the hot-drawing process parameters still need to be within a certain range. Otherwise, the pore structure of the hollow fiber membrane finally obtained deteriorates, and the service life and dimensional stability decrease.
[0193] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing a polyolefin hollow fiber membrane, characterized in that: The process steps include: S1, spinning, melt-extrude the polyolefin material, and form a semi-molded product with a hollow inner cavity under the action of a cavity-forming fluid; the polyolefin material is at least one of PP and PE, the glass transition temperature of the polyolefin material is Tg, and the melting point of the polyolefin material is Tm; S2, cooling and crystallizing, cooling and crystallizing the semi-formed product obtained in step S1, and winding it to obtain the primary fiber; S3, primary shaping, heat-setting the spun fiber obtained in step S2, and obtaining a heat-set semi-finished product after cooling; S4, cold drawing to form holes, cold drawing the heat-set semi-finished product obtained in step S3 to obtain a cold-drawn semi-finished product; wherein the cold drawing temperature is (Tg+30) to (Tg+80)°C, the cold drawing elongation is 20 to 40%, and the cold drawing rate is (10 to 30)% / min; S5, hot-drawing and hole-expanding, hot-drawing and hole-expanding the cold-drawn semi-finished product obtained in step S4 to obtain a hot-drawn semi-finished product; wherein the hot-drawing temperature is (Tm-60) to (Tm-30)°C, the hot-drawing elongation is 2 to 6 times the cold-drawing elongation, and the hot-drawing rate is not higher than 15% of the cold-drawing rate; S6, secondary shaping, subjecting the hot-drawn semi-finished product obtained in step S5 to secondary heat shaping to obtain a hollow fiber membrane.
2. The method for preparing a polyolefin hollow fiber membrane according to claim 1, characterized in that: In the step S3, The primary setting temperature is (Tm-60)~(Tm-20)℃; The time for one setting is 25 to 35 minutes; The primary fibers are stretched during the primary shaping process, and the stretching elongation is 0.5-2%.
3. The method for preparing a polyolefin hollow fiber membrane according to claim 2, characterized in that: In step S6, The temperature of the secondary setting temperature is higher than the temperature of the primary setting temperature, and the difference between the two is 10-20°C; The secondary shaping time is 0.5 to 3 minutes.
4. The method for preparing a polyolefin hollow fiber membrane according to claim 1, characterized in that: The polyolefin material is PP, In step S3, the primary setting temperature is 100-145°C; The primary fibers are subjected to a drafting process during the primary shaping process, and the drafting elongation is 0.8-1.2%; In step S6, the secondary setting temperature is 110-165°C.
5. The method for preparing a polyolefin hollow fiber membrane according to claim 4, characterized in that: In the step S4, Cold drawing to create holes is carried out in 2 to 4 steps; The cold drawing temperature is 20-40℃; The cold drawing draft ratio of each cold drawing is 104.7-118.3%; At the end of cold drawing, the line speed of the cold drawn semi-finished product is 2.5 to 3.5 m / min.
6. The method for preparing a polyolefin hollow fiber membrane according to claim 5, characterized in that: In the step S5, The hot drawing temperature is 110-130°C; Thermal stretching elongation is 90-110%; The hot drawing rate is (1-4.5)% / min.
7. The method for preparing a polyolefin hollow fiber membrane according to claim 1, characterized in that: In the step S5, Hot drawing and hole expansion are divided into 3 to 6 times; The hot drawing draft ratio of each hot drawing is 111.3-128.1%; At the end of hot drawing, the line speed of the hot drawn semi-finished product is 4.5-7.5 m / min.
8. The method for preparing a polyolefin hollow fiber membrane according to claim 1, characterized in that: The step S2 comprises the following steps: S21, natural cooling, cooling the semi-formed product obtained in step S1 by natural cooling to obtain a naturally cooled semi-finished product; the surface temperature of the naturally cooled semi-finished product obtained after natural cooling is Tm~(Tm+20)°C; S22, air cooling crystallization, air cooling crystallization is performed on the naturally cooled semi-finished product obtained in step S21 by means of air cooling, and then rolled up to obtain the spun fiber.
9. The method for preparing a polyolefin hollow fiber membrane according to claim 8, characterized in that: In the step S21, The path length for natural cooling is 30 to 1000 mm; The atmosphere during natural cooling is air or nitrogen, and the atmosphere temperature during natural cooling is 40-70°C; During natural cooling, the cooling rate of the semi-molded product surface is (0.05~0.6)℃ / mm@(100~200)m / min.
10. The method for preparing a polyolefin hollow fiber membrane according to claim 8, characterized in that: In step S22, The speed of cooling air flow is 30-60m / min; The temperature of the cooling air flow is 40-70°C; The path length of the slow cooling zone is 4 to 8 m.
Citation Information
Cited By
Preparation process of asymmetric polyolefin hollow fiber membrane for degassing
CN115738749A
Process for producing asymmetric polyolefin hollow fiber membrane for degassing
CN115738749B
